2022
DOI: 10.1017/s2045796022000130
|View full text |Cite
|
Sign up to set email alerts
|

Mental impact of Covid-19 among Spanish healthcare workers. A large longitudinal survey

Abstract: Aims Longitudinal data on the mental health impact of the coronavirus disease 2019 (Covid-19) pandemic in healthcare workers is limited. We estimated prevalence, incidence and persistence of probable mental disorders in a cohort of Spanish healthcare workers (Covid-19 waves 1 and 2) -and identified associated risk factors. Methods 8996 healthcare workers evaluated on 5 May–7 September 2020 (baseline) were invited to a second web-based survey (October–December 2020). Major depressive diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 66 publications
4
16
0
Order By: Relevance
“…We found that mental health problems were reported as frequently as life-threatening problems such as lack of training to avoid infection or PPE shortages, indicating that mental health problems are still considered relevant for HCWs almost 1 year after the first pandemic outbreak. This result is in line with evidence from longitudinal survey studies conducted in Spain ( 7 , 9 ) and abroad ( 10 , 47 , 48 ), showing that poor mental health outcomes among HCWs tend to persist over time. In a country where one in two nurses had thought of quitting their job since the beginning of the pandemic ( 49 ), the increased levels of tiredness and exhaustion reported by some of our interviewees serve as a plausible explanation for this sustained poor mental health (“[we] had not been allowed to disconnect or deactivate [since the beginning of the pandemic]”; “[HCWs] have got used to sleeping 3 h a day and being tired”).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that mental health problems were reported as frequently as life-threatening problems such as lack of training to avoid infection or PPE shortages, indicating that mental health problems are still considered relevant for HCWs almost 1 year after the first pandemic outbreak. This result is in line with evidence from longitudinal survey studies conducted in Spain ( 7 , 9 ) and abroad ( 10 , 47 , 48 ), showing that poor mental health outcomes among HCWs tend to persist over time. In a country where one in two nurses had thought of quitting their job since the beginning of the pandemic ( 49 ), the increased levels of tiredness and exhaustion reported by some of our interviewees serve as a plausible explanation for this sustained poor mental health (“[we] had not been allowed to disconnect or deactivate [since the beginning of the pandemic]”; “[HCWs] have got used to sleeping 3 h a day and being tired”).…”
Section: Discussionsupporting
confidence: 89%
“…Since the beginning of the COVID-19 pandemic, healthcare workers (HCWs) from pandemic hotspots around the world have reported mental health symptoms such as anxiety, depression, acute and posttraumatic stress, and insomnia ( 1 5 ). Pre-pandemic cohort studies are lacking, and we cannot know whether these problems were more prevalent after the COVID-19 outbreak ( 6 ); however, follow-up studies suggest that they might persist for at least 1 year ( 7 10 ), leading to exhaustion and resignation ( 11 ). With new variants and surges of the virus pressuring health systems worldwide ( 12 ) and concerning evidence of job quit and turnover ( 13 15 ), reducing the mental health toll of the pandemic on essential workers remains necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Training and the application of psychological first aid and referral to mental health resources should be provided as in-depth programs rather than trivial exercises in regulatory satisfaction [ 70 ]. This may be especially necessary in educators, as younger participants seem to experience a greater burden of symptoms that are associated with the development of PTSD [ 30 , 62 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Olga Lainidi 1 *, Eva Tzioti 2 , Maria Spiliou 3 , Panagiota Koutsimani 4 and Anthony Montgomery 5 1 University of Leeds, Leeds, UK 2 Mediterranean College, Thessaloniki, Greece 3 Aristotle University of Thessaloniki, Greece 4 University of Macedonia, Thessaloniki, Greece 5 Northumbria University, Newcastle, UK *Address all correspondence to: lndolga@gmail.com…”
Section: Author Detailsmentioning
confidence: 99%
“…More is known about the prevalence of panic attacks among healthcare professional after the COVID-19 pandemic compared with either pre-pandemic times or other occupations. Alonso et al, [5] in their longitudinal study on the impact of COVID-19 on Spanish healthcare workers, measured probable current mental disorders including major depressive disorder (MDD), Generalized Anxiety Disorder (GAD), Post-Traumatic Stress Disorder (PTSD), and Substance Used Disorders (SUDs) and work-related factors (e.g., care center preparedness, weekly working hours) among other variables. Panic attacks were measured as the number of panic attacks experienced in the 30 days prior to the interview.…”
Section: Introductionmentioning
confidence: 99%